Superconductivity: Discoveries and Discoverers Ten Physics Nobel Laureates Tell Their Story - Fossheim, Kristian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book is about the work of 10 great scientists; who they were and are, their personal background and how they achieved their outstanding results and took their prominent place in science history. We follow one of physics and science history's most enigmatic phenomena, superconductivity, through 100 years, from its discovery in 1911 to the present, not as a history book in the usual sense, but through close ups of the leading characters and their role in that story, the Nobel laureates, who were still among us in the years 2001-2004 when the main round of interviews was carried out. Since then two of them already passed away. For each one of the 10 laureates, the author tells their story by direct quotation from interviews in their own words. Each chapter treats one laureate. The author first gives a brief account of the laureates' scientific background and main contribution. Then each laureate tells his own story in his own words. This book is unique in its approach to science history.
The Ginzburg-Landau Theory of Superconductivity -- Magnetic Structure of Type II Superconductors -- The Microscopic Theory of Superconductivity -- The Microscopic Theory of Superconductivity -- Single Particle Tunnelling: Confirming the BCS-Theory -- Cooper Pair Tunnelling: The Josephson Effects -- Superconductivity from a Broader Perspective -- The Orsay Group on Superconductivity -- Discovery of Cuprate Superconductors -- Discovery of Cuprate Superconductors.
Keywords: Physics; Optical materials; Physics; Strongly Correlated Systems, Superconductivity; History and Philosophical Foundations of Physics; Low Temperature Physics; Optical and Electronic Materials